Fetal urinoma and prenatal hydronephrosis: how is renal function affected? - Oktar, Tayfun (Turk J Urol, 2013)
OBJECTIVE: In our study, the functional prognosis of kidneys with prenatal urinomas were investigated. MATERIAL AND METHODS: Between 2006 and 2010, fetal urinomas were detected in 19 fetuses using prenatal ultrasonography (US), and the medical records were reviewed retrospectively. Of the 19 cases, the follow-up data were available for 10 fetuses. The gestational age at diagnosis, prognosis of urinomas, clinical course and renal functions were recorded. Postnatal renal functions were assessed with renal scintigraphy. RESULTS: Unilateral urinomas and increased parenchyma echogenicity in the ipsilateral kidney were detected in all of the fetuses. Of the 10 fetuses with follow-up data, the option of termination was offered in 6 cases of anhydramnios, including 3 cases with signs of infravesical obstruction (a possible posterior urethral valve (PUV) and poor prognostic factors and 3 cases with unilateral hydronephrosis and increased echogenicity in the contralateral kidney. Only one family agreed the termination. The other 5 fetuses died during the early postnatal period. The average postnatal follow-up period in the 4 surviving fetuses was 22.5 months (8–38 months). One patient with a PUV underwent ablation surgery during the early postnatal period. In the postnatal period, none of the 4 kidneys that were ipsilateral to the urinoma were functional on scintigraphic evaluation. The urinomas disappeared in 3 cases. Nephrectomy was performed in one case due to recurrent urinary tract infections. CONCLUSION: In our study, no function was detected in the ipsilateral kidney of surviving patients with urinomas. Upper urinary tract dilatation accompanied by a urinoma is a poor prognostic factor for renal function.